Jumping plant-lice of the tribe Paurocephalini (Hemiptera: Psylloidea: Liviidae) in Brazil. - SERBINA, L. Š. (2025)
The predominantly tropical tribe Paurocephalini of jumping plant-lice currently consists of seven genera and 94 described species worldwide, of which the genera Klyveria Burckhardt et al. and Melanastera Serbina et al. have been recorded from Brazil with two and one species, respectively. here we review the taxonomy of the Brazilian species based on material collected from extensive fieldwork carried out in 15 states over the last decade. One species of Klyveria and 59 species of Melanastera are newly described, bringing the number of extant Klyveria spp. to three (both in Brazil and worldwide) and that of extant Melanastera spp. to 69 (60 in Brazil, 67 in the Neotropical region and one each in the Afrotropical and Oriental regions). The new species are described and illustrated, and identification keys for the Brazilian species are provided for adults and last instar immatures. The most diagnostically important structures are the distal segment of the aedeagus and the paramere, the forewing (shape, venation, surface spinules and colour pattern) and the female terminalia in the adults, and the chaetotaxy, tarsal arolium and shape of the additional pore fields on the caudal plate in the last instar immatures. The species descriptions are complemented by mitochondrial DNA barcodes (COI and cytB) and information on host plants. Klyveria spp. are restricted to Luehea (Malvaceae), while in Brazil 28 Melanastera spp. develop or are likely to develop on Melastomataceae, 18 spp. on Annonaceae, four spp. each on Asteraceae and Myristicaceae, and one species on Cannabaceae. Only three of the 63 species of Paurocephalini reported here from Brazil, are also known from other countries: two from Paraguay and one from Trinidad. Probably many morespecies of Melanastera are yet to be discovered and described. Priority in fieldwork should be given to areas that are at high risk of destruction or degradation by human activities, such as the Amazon rainforest, the Atlantic Forest and the Cerrado.